Mutational profile of TP53 in esophageal squamous cell carcinoma associated with chagasic megaesophagus - Lacerda, C. F. (2017)
Chaga's disease is an important communicable neglected disease that is gaining wider attention due to its increasing incidence worldwide. Achalasia due to chagasic megaesophagus (CM), a complication of this disease, is a known-yet, poorly understood-etiological factor for esophageal squamous cell carcinoma (ESCC) development. In this study, we aimed to perform the analysis of TP53 mutations in a series of Brazilian patients with ESCC that developed in the context CM (ESCC/CM), and to compare with the TP53 mutation profile of patients with benign CM and patients with nonchagasic ESCC. Additionally, we intended to correlate the TP53 mutation results with patient's clinical pathological features. By polymerase chain reaction (PCR) followed by direct sequencing of the hotspot regions of TP53 (exon 5 to 8), we found that TP53 mutations were present in 40.6% (13/32) of the ESCC/CM group, 45% (18/40) of the nonchagasic ESCC group, and in only 3% (1/33) of the benign CM group. Missense mutations were the most common in the three groups, yet, the type and mutated exon mutation varied significantly among the groups. Clinically, the groups exhibited distinct features, with both cancer groups (ESCC and ESCC/CM) been significantly associated higher consumption of alcohol and tobacco, older age, worse Karnofsky performance status, poor outcome than the patients with benign CM. No significant association was found between TP53 mutation profile and clinical-pathological features in any of the three groups. We describe first the time the analysis of TP53 mutations in ESCC that developed in the context of CM, and the observed high frequency of mutations, suggest that TP53 also plays an important role in the tumorigenic process of this unexplored etiological condition.